2020
DOI: 10.1364/boe.395547
|View full text |Cite
|
Sign up to set email alerts
|

Planar Airy beam light-sheet for two-photon microscopy

Abstract: We demonstrate the first planar Airy light-sheet microscope. Fluorescence light-sheet microscopy has become the method of choice to study large biological samples with cellular or sub-cellular resolution. The propagation-invariant Airy beam enables a tenfold increase in field-of-view with single-photon excitation; however, the characteristic asymmetry of the light-sheet limits its potential for multi-photon excitation. Here we show how a planar light-sheet can be formed from the curved propagation-invariant Ai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 33 publications
(50 reference statements)
0
27
0
Order By: Relevance
“…We anticipate the benefit demonstrated in this work can be obtained for any implementation of 2P-SPIM, including using Bessel [10,27,29] or Airy [31,32] beams instead of Gaussian beams, as long as the laser peak intensity remains lower than in the point-scanning case. The nonlinear photodamage threshold involved in 2P-SPIM using different beam shapes would however require further investigations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We anticipate the benefit demonstrated in this work can be obtained for any implementation of 2P-SPIM, including using Bessel [10,27,29] or Airy [31,32] beams instead of Gaussian beams, as long as the laser peak intensity remains lower than in the point-scanning case. The nonlinear photodamage threshold involved in 2P-SPIM using different beam shapes would however require further investigations.…”
Section: Discussionmentioning
confidence: 91%
“…In multiphoton light-sheet microscopy, adjusting the laser pulse frequency remains an attractive yet unexplored strategy to balance signal and photoperturbation. Indeed, most multiphoton light-sheet microscopes described so far [4,[10][11][12][13][25][26][27][28][29][30][31][32] were implemented using a mode-locked Ti:sapphire laser at f ∼80 Mhz, which is the most commonly used laser source in multitphoton microscopy. However, this choice is questionable and may not take full advantage of light-sheet illumination and its orthogonal geometry.…”
Section: Introductionmentioning
confidence: 99%
“…We have also demonstrated that rotation to a standard Airy beam profile gives a modest increase in the useable field of view, with no loss of resolution. Creation of an Airy beam profile in a light sheet microscope is straightforward to implement, either by the positioning and rotation of a cubic phase mask 17,52 or cylindrical lens 19,22 , or by design of SLM pattern 55 . Experimentalists using an Airy beam light sheet microscope should strongly consider use of the symmetric rotated Airy beam (SRA) beam profile rather than the standard Airy beam profile to realise the increase in useable FOV and resolution uniformity afforded by this beam type.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the empirical data showed that the FOV was extended slightly (4%) using the SRA profile, whilst it was reduced slightly (7%) in the NSRA profile, when compared to the Airy profile (Fig 1f; Airy, 130 µm; SRA 136 µm; NSRA 121 µm). Larger improvements to effective FOV are expected when using different combinations of objective and Airy beam profile, with an improvement of up to 33% demonstrated 52 .…”
Section: Symmetrical Rotated Airy Improves Resolution Across Fovmentioning
confidence: 99%
See 1 more Smart Citation